2011
DOI: 10.1016/j.vaccine.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Robust antigen-specific humoral immune responses to sublingually delivered adenoviral vectors encoding HIV-1 Env: Association with mucoadhesion and efficient penetration of the sublingual barrier

Abstract: The efficient induction of virus-specific mucosal antibodies is an important unmet objective in Human Immunodeficiency Virus Type-1 (HIV-1) vaccine research. One promising approach is sublingual (SL) immunization. We examined the effectiveness of SL delivery of two different viral vectors: (i) a recombinant adenovirus (rAd5), and (ii) a Herpes Simplex Virus Type-1 amplicon vector (HSV-1). Initial in vitro videomicroscopy experiments showed that rAd5 particles were trapped in saliva (i.e., that Ad5 was mucoadhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Antibodies can protect humans against central nervous system infection , and recombinant adenoviruses have been shown to elicit robust antigen‐specific serum IgG antibody responses to transgenes . In our study, we developed recombinant replication‐defective adenoviruses to deliver gD2 alone, ΔUL25 alone or the gD2ΔUL25 fusion protein for comparison with FI‐HSV2 in terms of immunogenicity and protective efficacy against HSV‐2 challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies can protect humans against central nervous system infection , and recombinant adenoviruses have been shown to elicit robust antigen‐specific serum IgG antibody responses to transgenes . In our study, we developed recombinant replication‐defective adenoviruses to deliver gD2 alone, ΔUL25 alone or the gD2ΔUL25 fusion protein for comparison with FI‐HSV2 in terms of immunogenicity and protective efficacy against HSV‐2 challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Sublingual immunization with rAdV encoding the conserved influenza nucleoprotein antigen [28] or the soluble globular head of hemagglutinin [29] protected mice against influenza virus infection. Furthermore, sublingual administration of rAd5 vectors encoding HIV proteins induced both significant antigen-specific humoral (serum and mucosal IgG and IgA) [30] and cellular (systemic and mucosal CTL responses) [31] immune responses. Moreover, sublingual vaccination with rAdV encoding a truncated S protein (rAdV-S), which is a major antigenic protein present on severe acute respiratory syndrome-associated coronavirus (SARS-CoV), induced systemic neutralizing antibodies and airway IgA antibody responses in mice.…”
Section: Recombinant Virus Based (Rna-) Vaccinesmentioning
confidence: 99%
“…Sublingual immunotherapy has been widely used for therapeutic allergy vaccines. 25 Although several studies have showed the efficiency of the sublingual route to induce tolerance, others have observed cell-mediated immune responses against pathogens, [26][27][28][29] or tumors. 30 Similarly, Sandoval et al have reported that the IN route was able to induce good antitumoral responses in a model of oral cancer and lung.…”
Section: Discussionmentioning
confidence: 99%